Radioactive Background of Granito Madeira, North Amazonas, Brazil (Brazilian Journal of Radiation Sciences, 2019)
Radionuclides of natural origin are present in rocks and soils but have no homogeneous distribution in the soil of the Earth. Volcanic rocks have a higher concentration of uranium and thorium. Thus, sites with this type of origin present as radiological abnormalities. An example is the Planalto de Poços de Caldas in Minas Gerais. Another example is the Granito Madeira - a rock formation located in the Amazonas State, 350 km north of Manaus. This work presents the results of the natural radiation monitoring of Granito Madeira. 30,000 dose rates were collected with a sodium iodide scintillator transported on tracks within the Floresta Amazônica. These data were treated and georeferenced. As a result, an annual dose relative to gamma radiation of 6.0 mSv.year-1 was obtained. This information was represented in a frequency histogram and in a map of Granito Madeira.